Skills for competitiveness: an empirical analysis of the educational provision for oenologists offered by Italian universities. Issue 2 (15th March 2023) - Borsellino, Valeria; Carta, Valentina; Varia, Francesca
ABSTRACT: Purpose: Whilst operating in the context of a high-income economy, the Italian labour market is affected by the considerable challenges of vertical mismatch, skill gaps and skill shortages. In such a context, the aim of this empirical study is to explore current university provision regarding the formal qualification of the oenologist, in order to assess its alignment with the professionalism demands from the wine sector. Design/Methodology/Approach: The following was deployed to analyse university provision with a mixed method approach including social network analysis, cluster analysis and desk analyses based on descriptive statistics. Findings: The comparative analysis outlined in the research on the basis of different educational activities shows that some degree courses would appear to be interchangeable. Furthermore, the study also shows a partial alignment between university educational provision and the skills required by stakeholders, thereby demonstrating the need to make changes in study programmes. Practical implications: The authors hope that the evidence-based suggestions proffered herein may be used as a scientific basis to support the formulation of education policy at the ministerial level and as a guideline to plan and update academic curricula. Theoretical implications: This research contributes to the scientific debate relating to the educational preparation of university graduates and their employability according to the requirements of the professional wine sector. It enriches the theoretical framework of evidence-based educational research, offering alternative avenues for interpretation about the similarity profiles of educational provision. Originality/Values: To the best of our knowledge, the research laid out in this paper is innovative in the field of educational literature due to its use of different methodologies and techniques to obtain results, thereby proposing a wider and alternative use of well known analytical methods.